A new synonym and distribution record in the genus Ceiupaba Martins & Galileo, 1998 (Coleoptera, Cerambycidae, Lamiinae, Desmiphorini) - Bezark, Larry G.; de L. Nascimento, Francisco E. (Zootaxa, 2019)
Mimasyngenes piauiensis Galileo, Martins & Nascimento 2014, is proposed as a synonym of Ceiupaba lineata Martins & Galileo, 1998, and the distribution is expanded to include Paraguay. The sex of the holotype of M. piauiensis is corrected to female.